Kun sota on ohi : sodista selviytymisen ongelmia ja niiden ratkaisumalleja 1900-luvulla - Karonen, Petri (Historiallinen arkisto, 2006)
Abstract: When the war is over : management of the aftermath of wars and models of solving post war challenges in the 20th century.